Effect of different decontamination agents on the bond strength of CAD/CAM blocks and repair composite materials = Efecto de diferentes agentes descontaminantes sobre la resistencia de unión de bloques CAD/CAM y resinas compuestas - Kopuz, Dilan; İlgi Sancak, Elif; Tekçe, Neslihan (2024)
The purpose of this study was to examine the effect of different decontamination agents on the bond strength of saliva-contaminated CAD/CAM blocks and repair composite materials. Two hunderd eighty 3-mm-thick specimens were prepared from four different CAD/CAM materials: Katana Zirconia UTML disc, IPS e.max CAD block, Shofu block, and Vita Enamic block. Each material was divided into seven different subgroups (N=70). Group 1 had a clean surface. The other groups were comprised of the samples, which were contaminated with human saliva: group 2: negative control (non-cleaned); group 3: cleaned with water spray; group 4: cleaned with 70% ethanol; group 5: cleaned with Ivoclean; group 6: cleaned with Katana Cleaner; and group 7: cleaned with phosphoric acid. After the decontamination protocols, the resin composite cylinders were bonded to the CAD/CAM surfaces with a thin layer of dual-cured resin cement. The samples were stored for 24 hours at 37°C in distilled water. Then, they were subjected to a shear bond strength test (SBS). The values were recorded, and fracture types were evaluated using a microscope. Data were analyzed using two-way ANOVA and Tukey's post-hoc test. Generally, all decontaminating agents improved the SBS of composites to Katana Zirconia UTML, IPS e.max, and Vita Enamic materials (p<0.05). However, for Shofu materials, group 6 samples exhibited significantly higher bond strength values as compared with group 2 samples (p=0.026). The highest SBS values were seen in the phosphoric acid-treated group in Katana zirconia materials (26.45 ± 9.38 MPa), whereas the lowest values were seen in group 2 samples in Shofu materials (13.17 ± 3.40 MPa). Each decontaminant agent improved the bond strength of composites to the contaminated CAD/CAM materials. If saliva is not cleaned before adhesive procedure, SBS values may decrease. All decontamination agents can be used safely on zirconia, lithium-disilicate glass-ceramic, hybrid ceramic...
El propósito de este estudio fue examinar el efecto de diferentes agentes descontaminantes sobre la fuerza de unión de bloques CAD/CAM contaminados con saliva y materiales compuestos de reparación. Se prepararon doscientas ochenta muestras de 3 mm de espesor a partir de cuatro materiales CAD/CAM diferentes: disco Katana Zirconia UTML, bloque IPS e.max CAD, bloque Shofu y bloque Vita Enamic. Cada material se dividió en siete subgrupos diferentes (N=70). El grupo 1 tenía una superficie limpia. Los otros grupos estaban compuestos por muestras que estaban contaminadas con saliva humana: grupo 2: control negativo (no limpio); grupo 3: limpiado con agua pulverizada; grupo 4: limpiado con etanol al 70%; grupo 5: limpiado con Ivoclean; grupo 6: limpiado con Katana Cleaner; y grupo 7: limpiado con ácido fosfórico. Después de los protocolos de descontaminación, los cilindros de composite de resina se adhirieron a las superficies CAD/CAM con una fina capa de cemento de resina de curado dual. Las muestras se almacenaron durante 24 horas a 37°C en agua destilada. Luego, fueron sometidos a una prueba de resistencia al corte (SBS). Se registraron los valores y se evaluaron los tipos de fracturas utilizando un microscopio. Los datos se analizaron mediante ANOVA de dos factores y la prueba post-hoc de Tukey. En general, todos los agentes descontaminantes mejoraron el SBS de los composites con los materiales Katana Zirconia UTML, IPS e.max y Vita Enamic (p<0,05). Sin embargo, para los materiales Shofu, las muestras del grupo 6 exhibieron valores de fuerza de unión significativamente más altos en comparación con las muestras del grupo 2 (p=0,026). Los valores más altos de SBS se observaron en el grupo tratado con ácido fosfórico en materiales de circonio Katana (26,45 ± 9,38 MPa), mientras que los valores más bajos se observaron en las muestras del grupo 2 en materiales Shofu (13,17 ± 3,40 MPa). Cada agente descontaminante mejoró la fuerza de unión...
En revista Odóvtos, vol. 26, no.1 (enero-abril 2024)
Descripción basada en el contenido visto el 22 de enero, 2025
También disponible en formato HTML y EPUB